Viral DNA·RNA Hybrids in Cells Infected with Simian Virus: The Simian Virus 40 Transcriptional Intermediates - Girard, Marc (1974)
Brief labeling of cells infected with simian virus 40 with tritiated uridine resulted in the incorporation of part of the label into material that was soluble in 1 M NaCl and sensitive to KOH, with a buoyant density close to that of DNA. The properties of this material suggest that it represents single-stranded nascent molecules of messenger RNA of simian virus 40 hydrogen-bonded over a small portion of their length to viral DNA templates. The name “simian virus 40 transcriptional intermediate molecules” is suggested for these naturally occurring DNA·RNA hybrid molecules. The DNA in the hybrid seems to be in the form of replicative intermediate molecules.